Effect on the parameters of the high-heel shoe and transfer time of ground reaction force during level walking - Hyun, Seung-Hyun; Kim, Young-Pyo; Ryew, Che-Cheong (Journal of exercise rehabilitation, 2016)
This study aimed to analyze an effect on the parameters of high-heel shoe and transfer time of ground reaction force during level walking and subjects participated were composed of adult female subjects (n=13) of 20s with height of high heel (0 cm, 9 cm, respectively). Instru-ment used for the study was 1 set force plate (AMTI-OR9-7) and sam-pling rate for data collection of analysis parameters was set-up at 1,000 Hz. The revelation of required coefficient of friction (RCOF) maximum showed significant difference with more rapid than that of 1st peak ver-tical force (1 PVF). Transfer time of body weight showed significant dif-ference with more delay at 9 cm than that of 0 cm. RCOF required more frictional force required because PVF showed significant difference with larger value on 9 cm than that of 3 cm at 1 PVF. Both center of pressure (COP) x and COPy showed rather less displacement on 9 cm than that of 0 cm. In addition, level walking by high heel shoe did not control efficiently the ground reaction force due to restricted control capacity of coefficient of frictional force and therefore could suggest an inducement of muscle fatigue, heightening a possibility of sliding and falling due to decrease of frictional force.